2016
DOI: 10.1007/s40122-016-0044-3
|View full text |Cite
|
Sign up to set email alerts
|

The AC/AG Diplotype for the 118A>G and IVS2 + 691G>C Polymorphisms of OPRM1 Gene is Associated with Sleep Quality Among Opioid-Dependent Patients on Methadone Maintenance Therapy

Abstract: Introduction Methadone is a full agonist of the opioid receptor mu 1 which is encoded by the OPRM1 gene. Sleep disorders were frequently reported by opioid-dependent patients during methadone maintenance therapy (MMT). It is possible, therefore, that genetic polymorphisms in OPRM1 influence sleep quality among patients on MMT. This study investigated the association of OPRM1 polymorphisms with sleep quality among opioid-dependent patients on MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…It has been previously demonstrated that the AC/ AG diplotype for the 118A>G and IVS2+691G>C polymorphisms of OPRM1 is associated with better sleep quality among opioid-dependent patients on MMT (Zahari et al, 2016a). However, in opioid-naive individuals, no significant difference of the mean PSQI scores was observed between subjects with the AC/AG diplotype and those without this diplotype (p = 0.368).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been previously demonstrated that the AC/ AG diplotype for the 118A>G and IVS2+691G>C polymorphisms of OPRM1 is associated with better sleep quality among opioid-dependent patients on MMT (Zahari et al, 2016a). However, in opioid-naive individuals, no significant difference of the mean PSQI scores was observed between subjects with the AC/AG diplotype and those without this diplotype (p = 0.368).…”
Section: Discussionmentioning
confidence: 93%
“…Allele-specific multiplex polymerase chain reaction (PCR) was used to detect OPRM1 polymorphisms [118A>G (dbSNP rs1799971) and IVS2+691G>C (dbSNP rs2075572)] (Mohamed Nazar, 2013; Zahari et al, 2015;Zahari et al, 2016b, Zahari et al, 2016a. All reactions were performed on the Applied Biosystems  Veriti  96-Well Thermal Cycler (Applied Biosystems, USA).…”
Section: Genotyping Methods For Detection Of Oprm1 Polymorphismsmentioning
confidence: 99%
“…Concerning genetic factors for sleep disturbance–related side effects of opioids, thus far, only two studies have been conducted among opioid-addicted individuals during methadone treatment. In both studies (i.e., by Wang et al [ 13 ] and Zahari et al [ 11 ]), the OPRM1 polymorphisms have been shown to be associated with methadone-related sleep problems. Wang et al [ 13 ] reported a significant association of OPRM1 polymorphisms with insomnia side effects in a Taiwanese MMT cohort.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported detailed methods of this study sample previously. [ 1 5 6 7 8 9 10 11 12 , 32 32 34 ] Data used in this study were collected as part of the study to evaluate the application of personalized methadone therapy among patients on MMT. In this cross-sectional study, a total of 148 subjects were recruited from 11 outpatient methadone clinics in Kelantan, Malaysia between March and October 2013.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
See 1 more Smart Citation